Developing lay summaries and thank you notes in paediatric pragmatic clinical trials. (4th March 2022) - Zimmerman, Kanecia O.; Perry, Brian; Hanlen‐Rosado, Emily; Nsonwu, Adora; Lane, Morgan D.; Benjamin, Daniel K.; Becker, Mara; Corneli, Amy; ,
Abstract: Introduction: Better transparency of research results and participant engagement may help address poor participant accrual in paediatric clinical research. We conducted formative research to assess the acceptability of lay summaries and thank you notes, as well as to refine and expand guidance on participant and family engagement in Pediatric Trials Network's (PTN) pragmatic paediatric clinical research. Methods: Informed by draft PTN guidance, we conducted in‐depth qualitative interviews with adolescent clinical trial participants and caregivers of paediatric participants in four trials conducted by PTN across eight sites. Participants were shown multiple versions of mock lay summaries and thank you notes and asked questions on their preferences for content and layout, and on trial communications. We used applied thematic analysis to analyse the data. Results: We interviewed 27 individuals engaged in PTN research: 24 caregivers and 3 adolescents. During a trial, participants want regular updates on study progress, reminders of the study purpose and reassurances of data confidentiality. After the trial, participants want to learn the aggregated results, particularly medication effectiveness. Participants reported that lay summaries should include a review of the study's purpose, methods and length, and that they expect to learn individual‐level results. Participants stated that thank you notes must be of sufficient length to be meaningful. Conclusions: This is the first study to describe stakeholder preferences for thank you note content and layout. Using these findings, we finalized PTN's trial communication guidance for use in future PTN trials. Research is needed to determine the effect of lay summaries and thank you notes on improving public transparency regarding clinical trials and paediatric trial recruitment and completion. Patient or Public Contribution: By design, stakeholders (adolescent trial participants and caregivers of pediatric trial participants) contributed to PTN's guidance on the content and layout of lay summaries and thank you notes through their participation in the in‐depth interviews.